Digital technology and innovation: the impact of blockchain application on enterprise innovation - Li, Zhaochen; Xu, Zimu (Elsevier, 2025)
Blockchain as a frontier digital technology provides new opportunities for innovation. This paper builds a theoretical framework utilizing the Resource-Based View (RBV), and empirically examines the impact of blockchain application on enterprise innovation, based on panel data from Chinese listed companies spanning from 2007 to 2020. This paper finds that the adoption of blockchain applications significantly promotes enterprise innovation, through mechanisms of improving operational efficiency and expanding operational scope. With regard to contextuality, the positive effect of blockchain applications on innovation is more pronounced in enterprises with higher levels of technological and capital accumulation. With regard to temporality, innovation at faster paces can better realise the benefits of blockchain applications. This paper provides robust empirical evidence derived from a large sample, thereby enhancing our understanding of this dynamic relationship and suggesting directions for future research.
Keywords: Business & Management; 3503 Business systems in context; 3507 Strategy, management and organisational behaviour